Incomplete‐Market Equilibria Solved Recursively on an Event Tree - DUMAS, BERNARD; LYASOFF, ANDREW (Journal of Finance, 2012)
ABSTRACT Because of non‐traded human capital, real‐world financial markets are massively incomplete, while the modeling of imperfect, dynamic financial markets remains a wide‐open and difficult field. Some 30 years after Cox, Ross, and Rubinstein (1979) taught us how to calculate the prices of derivative securities on an event tree by simple backward induction, we show how a similar formulation can be used in computing heterogeneous‐agents incomplete‐market equilibrium prices of primitive securities. Extant methods work forward and backward, requiring a guess of the way investors forecast the future. In our method, the future is part of the current solution of each backward time step.